USE OF VEGETABLE RAW MATERIALS IN THE TECHNOLOGY OF FUNCTIONAL MAYONNAISE SAUCES - АРТЕМ, ANTONENKO; BAL-PRYLYPKO, LARYSA (Herald of Khmelnytskyi National University. Technical sciences, 2025)
New generation food products are products with a balanced composition and ratio of biologically valuable substances that contribute to maintaining health, increasing the body's resistance to stress and negative environmental influences. Today, the development of innovative technologies in the field of healthy nutrition, in particular based on emulsions, is based on the use of traditional and non-traditional raw materials with a high content of biologically and physiologically valuable components. This makes it possible to create products that act directly on certain organs and systems of the human body. The main goal of the study is to develop a recipe and technology for manufacturing mayonnaise sauces with a given particle size of the dispersion phase that are resistant to thermal oxidation. This involves the use of stabilizers of natural origin and the addition of plant raw materials to give the product functional properties. The article presents the results of marketing research related to the consumption of mayonnaise products by the population. The survey showed that over 59% of respondents prefer products made from safe natural components, in particular, structure-forming agents, emulsifiers and flavoring additives. It is proposed to use gum arabic to enrich mayonnaise sauces with useful plant substances and improve their organoleptic characteristics. It is also noted that it is advisable to use a protein-fat additive as a stabilizer and emulsifier of natural origin in the production of mayonnaise sauces. The rheological properties of aqueous suspensions have been studied. The addition of gum arabic will allow to purposefully influence the mechanisms of formation and stabilization of emulsions, change their viscosity and increase resistance to thermal oxidation. It has been proven that a protein-fat additive reduces the surface tension of the system with the help of the functional groups present. It has been shown that heating an aqueous suspension of a protein-fat additive increases surface activity by 1.5 times compared to an aqueous suspension obtained under normal conditions. The obtained research results confirm the possibility and feasibility of using gum arabic, protein-fat additive and gum arabic in the technology of manufacturing mayonnaise sauces. A comprehensive evaluation of the new mayonnaise sauce, including a study of the organoleptic characteristics of the samples, showed an improvement in individual indicators, which gives grounds to consider the developed recipe competitive.
Keywords: sauces; vegetable hydrocolloids; protein-fat supplement; gum arabic; dietary fiber; biotechnology; technology